Understanding Visitor Engagement at Private Art Spaces: A Mixed-Methods Study of A Non-Profit Gallery in Indonesia - Indraputri, Zafira Meizzati; Astuti, Novika Candra (Yayasan Riset dan Pengembangan Intelektual, 2026)
Private art spaces occupy an unusual position in the cultural landscape. They carry public-facing missions—education, cultural dialogue, community building—yet operate without the institutional funding that sustains government museums. This study examines factors shaping visitor engagement at Gallery XYZ, a non-profit contemporary art institution located in a major creative city in Indonesia. Despite years of programming exhibitions, workshops, and cultural events, the gallery faces inconsistent attendance and a narrow visitor demographic. The research employed a convergent mixed-methods design, integrating quantitative survey data (n=162) with qualitative semi-structured interviews (n=11). Survey respondents were categorized into three segments: current visitors (n=88), aware non-visitors who recognized the gallery but had never attended (n=34), and those entirely unaware of its existence (n=40). Thematic analysis following Braun and Clarke's framework identified six interrelated themes: motivational drivers, engagement barriers, visitor experience quality, brand perception, communication effectiveness, and value perception. Quantitative findings revealed that 81.8% of visitors were irregular—either lapsed or one-time attendees. Access and distance emerged as the dominant barrier (67.0% of visitors, 31.1% of non-visitors). The companion dependency pattern proved equally notable: 61.4% visited with friends, while 25-31% across segments cited lacking a companion as a barrier. Qualitative findings revealed a perception gap—the gallery commanded prestige among art insiders yet remained largely invisible to the general public. Non-visitors described galleries as spaces